A MODEL FOR VISCOUS MAGMA FRAGMENTATION DURING VOLCANIC BLASTS - Alidibirov M.A. (My University, 1994)
Fragmentation of magma containing gas bubbles is of great interest in connection with developing models for the formation of pyroclastics and for volcanic blasts (explosions). This paper considers the problem of fragmentation of highly viscous (>108 Pa s) or solidified magma containing bubbles with excess gas pressure. It is suggested that the fragmentation of magma be considered on the basis of the fragmentation wave theory proposed by Nikolsky and Khristianovich, which is generally applicable to gas-dynamic phenomena occurring in mines. Then it becomes possible to derive the equations of conservation for the fragmentation wave front which moves into a body of magma from its free surface. As a result, the velocity, N, of magma fragmentation, and the velocity, u, of the movement of the gas-pyroclastic mixture behind the fragmentation wave front, are determined. Calculations show that N can reach 5 m/s. Therefore the duration of the fragmentation of the magma body (blast duration) proves to be long. The suggested model explains the possibility of several explosions during the blast as a result of the fragmentation wave stopping, and accounts for the angular shape of pyroclasts by the brittle disruption of interbubble partitions during fragmentation wave propagation through the porous magma body. The initiation and cessation of fragmentation are defined by magma porosity, magma tensile strength, and the pressure differential between gas pressure in pores and the atmospheric pressure. The physical model of magma fragmentation developed explains the mechanism of energy release during volcanic blasts of the Vulcanian or Pelean types.